FIBROUS DYSPLASIA IN THE MAXILLO-MANDIBULAR REGION - case report - Radka Cholakova; P. Kanasirska; N. Kanasirski; Ivan Chenchev; Atanaska Dinkova (Peytchinski Publishing, 2010)
Craniofacial fibrous dysplasia is 1 of 3 types of fibrous dysplasia that can affect the bones of the craniofacial complex, including the mandible and maxilla.Fibrous displasia is a skeletal developmental disorder of the bone-forming mesenchyme that manifests as a defect in osteoblastic differentiation and maturation. It is a lesion of unknown etiology, uncertain pathogenesis, and diverse histopathology. Fibrous dysplasia represents about 2, 5% of all bone tumors and over 7% of all benign tumours.The aim of this article is to represent a rare case of bilateral fibrous dysplasia of the upper and lower jaws, in combination with Intellectual disability (previously called mental retardation). The clinical diagnostic approach including imaging studies: Orthopantomogram (OPG) and 3D tomography is described. Histological examination was also essential for obtaining a definitive diagnosis.